Natural Disaster Response : Lessons from Evaluations of the World Bank and Others - Todd, David; Todd, Hazel (World Bank, Washington, DC, 2017)
This document aims to provide a concise collection of those good practices and challenges that have recently been identified by evaluative work on natural disaster response of the World Bank, the Independent Evaluation Group (IEG), and other major actors. It is hoped that the lessons identified can be used by World Bank staff engaged in work related to natural disasters, to gain insights into approaches that may promote or hinder effective assistance to partner countries. Although great international attention is focused on the occurrence of disasters and the short term response to them, this phase is only part of the overall disaster management cycle. This cycle includes three main phases pre-disaster, disaster response, and post-disaster each of which has an appropriate range of activities. Evaluations have provided many lessons for this phase. However, these generally also carry over into the post-disaster phase, and even further into the next pre-disaster phase. Some of the lessons may partially contradict each other (for example, the value of local participation may cut across the benefits of speedy action), which means that trade-offs must be developed for each specific situation.